Forbush Decrease Characteristics in a Magnetic Cloud - A. S. Petukhova; I. S. Petukhov; S. I. Petukhov (Space Weather)
Abstract Based on the new mechanism, the Forbush decrease characteristics are calculated for eight magnetic cloud types. It is shown that the Forbush decrease amplitude does not depend on the magnetic cloud type, while the anisotropy strongly does. The Forbush decrease spectrum for (2–150 GV) rigidities is calculated for the first time. The Forbush decrease amplitude for low rigidities is ∼100%, which can be explained by a large number of forbidden particle trajectories. The Forbush decrease amplitude rapidly decreases for high rigidities due to the geometric condition. Comparing the calculated Forbush decrease characteristics with measurements for two events shows that the Forbush decrease amplitudes agree with the measurements quantitatively, and the anisotropies do qualitatively.